USE OF REMINDER AS NUDGE TO INCREASE EMPLOYEE PARTICIPATION TO COMPLETE DATA IN DITJENPAS CIVIL SERVANTS SYSTEM - Ekha Nurfitriana; Maki Zaenudin S (Polteknik Ilmu Pemasyarakatan, 2019)
We tested the use of reminder techniques to increase participation of Sekertariat Direktorat Jenderal Pemasyarakatan employeesi to complete and update their staffing data independently through the design of one group pre-post test. We weight the completeness of data from each employee based on information categories. Those who are still incomplete are then given a reminder in the form of a circular to immediately complete the staffing data. We find that there is an increase in completeness of data from an average number of completeness 64.94% to 75,22%. Paired sample t-test results show that there is a significant difference (t = 24.198; n = 176; p<0.0005; d= .77) between conditions before and after the intervention is given to employees.